PENGARUH LATIHAN PLIOMETRIK MENGGUNAKAN BOKS TERHADAP PRESTASI LOMPAT JAUH DI STKIP PASUNDAN CIMAHI - Triono, Sandi Dwi (Jurnal Olahraga, 2016)
This study aims to determine the effect of plyometric training using boxes on the long jump achievement of students at STKIP Pasundan. The research method used to uncover these problems through the experimental method with pre-test design and post-test design. The sample of this study was 20 students from PJKR STKIP Pasundan Cimahi who participated in the Athletic UKM activities in STKIP Pasundan Cimahi. The study was conducted 3 meetings each week for 6 weeks. The instrument used is the long jump test which has been tested for validity and reliability. The data obtained were processed using the T-Paired test. The results of the study revealed that there was a difference in effect between plyometric training programs using boxes and plyometric exercises that did not use boxes. Plyometric exercises using boxes have a more significant effect compared to plyometric exercises without using boxes on long jump achievements